Impact of Counselling on Customer Retention in The Pharmaceutical Industry: A Case in Ashanti Region - Rajendrakumar Muljibhai Parmar, Faustina Anyamesem-Poku, (European Economic Letters (EEL), 2024)
Doing business these days has become complex and sophisticated due to several factors of which the nature of the competition plays a commanding role. In every industry, people use up-to-the-second approaches to facilitate business processes to drive home and retain customers. The reason is that, to the majority, effective customer retention is the only way in which a business can survive and/or outwit its competitors. In the pharmaceutical industry, retaining customers is very important to take the business to the next level. Amidst the various strategies, the paper investigated the role of counseling and its impact on customers to ascertain whether it is a strategy worthy of committing resources. The researcher examined the relationship between the industry players and the customers, and the place of counseling; using a descriptive survey type based on quantitative analysis to ensure good customer service. Focusing on counseling and its impact secondary data was analyzed based on the sample population of 350, comprising 6 selected pharmacies, 100 pharmacy attendants, and 250 customers from these pharmacies. The results of this investigation were synthesized based on the collective findings delineated in preceding studies. The analysis revealed a robust correlation between customer services and the quality of work delivered. This noteworthy underscored the premise that an elevation in service quality is conducive to higher customer satisfaction and loyalty. Because of that counseling services must be attached to pharmacy attendants as the determinants of service quality to ensure customer retention. The findings of this study elucidate that, amidst an intensely competitive landscape, the retention of existing customers is paramount for achieving market success. The paper recommended that to facilitate customer retention, it is imperative to adopt a customer-centric approach. Emphasizing such a paradigm is essential, as organizations that prioritize customer needs are likely to focus on delivering high-quality services promptly. Therefore, there is a need to provide effective guidance and counseling services in pharmaceutical shops to increase customer satisfaction. The reason is making this the highest priority, which has a greater impact on both the internal marketers and the customers, and thus constitutes one of the most critical variables influencing customer retention.